Effects of plyometric compared to high-intensity interval training on youth female basketball player`s athletic performance - Haghighi, A. H.; Hosseini, S. B.; Askari, R.; Shahrabadi, H.; Ramirez-Campillo, R. (Sport Sciences for Health, 2024)
Purpose To improve basketball players` athletic performance, effective and optimal training programs are needed. The study aim was to compare the effects of 6 weeks of plyometric training (PT) to high-intensity interval training (HIIT) on youth female basketball player`s athletic performance.